Risk Score for Prolonged Mechanical Ventilation in Coronary Artery Bypass Grafting - Dallazen-Sartori,Fernanda (2021)
Abstract Background Prolonged mechanical ventilation (MV) after cardiac surgery imposes a significant burden on the patient in terms of morbidity and financial hospital costs. Objective To develop a risk score model to predict prolonged MV in patients undergoing coronary artery bypass grafting (CABG) surgery. Methods This was a historical cohort study of 4165 adult patients undergoing CABG between January 1996 and December 2016. MV for periods ≥ 12 hours was considered prolonged. Logistic regression was used to examine the relationship between risk predictors and prolonged MV. The variables were scored according to the odds ratio. To build the risk score, the database was randomly divided into 2 parts: development data set (2/3) with 2746 patients and internal validation data set (1/3) with 1419 patients. The final score was validated in the total database and the model's accuracy was tested by performance statistics. Significance was established at p < 0.05. Results Prolonged MV was observed in 783 (18.8%) patients. Predictors of risk were age ≥ 65 years, urgent/emergency surgery, body mass index ≥ 30 kg/m2, chronic kidney disease, chronic obstructive pulmonary disease, and cardiopulmonary bypass time ≥ 120 minutes. The area under the ROC curve was 0.66 (95% CI, 0.64-0.68; p<0.001), the Hosmer-Lemeshow chi-square test was χ2: 3.38 (p=0.642), and Pearson's correlation was r = 0.99 (p<0.001), indicating the model’s satisfactory ability to predict the occurrence of prolonged MV. Conclusion Selected variables allowed the construction of a simplified risk score for daily practice, which may classify the patients as having low, moderate, high, and very high risk. (Int J Cardiovasc Sci. 2020; [online].ahead print, PP.0-0